THE DEVELOPMENT OF MORALS REASONING USING SOCIOSCIENTIFIC ISSUE - BASED TEACHING WITH ARGUMENTATION TECHNIQUE IN THE S 33101 SOCIAL STUDIES OF GRADE 12 STUDENTS - Sudcha, Anumat; Tungkasamit, Angkana (Journal for Developing the Social and Community, 2023)
The objectives of the study were 1) The students provided moral reasons higher than the 4th concept of Kohlberg and students passed beyond 70%. 2) To develop learning achievement using the SocioscientiIfic Issue - Based Teaching With Argumentation Technique in social studies the standards that mean achievement and students passed beyond 70%, the students had 70% of studying. The target group of this research was 38 of the 12th grade students studying at Borabuwittayakhan School in the second semester of the academic year 2022. This study was an action research, and the instruments used in the study consisted of 1) a learning plan by SocioscientiIfic Issue - Based Teaching With Argumentation Technique as a tool applied in experiment, 2) a record form of results, an observation form, an interview form for students, and a quiz as tools used in reflecting, and 3) a test on moral reasons skills and a test for learning achievement as tools used in evaluating the effectiveness of learning management. All collected data were analyzed by using Mean, Standard Deviation and Percentage. Research findings: The Moralitle reasons provided Utilizing enhancement of students averaged 4.38 with was higher than the 4th of Kohlberg concept and The students passed the standards 28 that meant 73.68% with was higher than the standards that the 4th concept of Kohlberg and students passed beyond 70%. 2. In terms of learning achievement averaged 21.97 with passing the criteria, representing 73.23% and the students passed 27 about 71.05% with was higher was than the standards that mean achievement and students passed beyond 70%, the students had 70% of studying.